The extended mind hypothesis: an anti-metaphysical vaccine - Airoldi, Giorgio (Sofia, 2019)
Discussions about the extended mind have ‘extended’ in various directions in the last decades. While applied to other aspects of human cognition and even consciousness, the extended-mind hypothesis has also been criticized, as it questions fundamental ideas such as the image of a dual world, divided between an external and an internal domain by the border of ‘skin and skull’, the idea of a localized and constant decision center, and the role of internal representations. We suggest that the main virtue of the hypothesis is not as a theory per se, but as a vaccine against persistent metaphysical prejudices about the mind’s structure, functions and borders. Being an hypothesis about the most efficient ways to combine resources and problems, and not a theory about the mind’s a-priori constitution, the extended mind view moves the focus from ontology to pragmatics and helps purify philosophy of mind from metaphysical remainders.